Analysis by tree diagram in Northern Kurdish – Behdini Local Dialect - Omer Ahmed, Baiz (Journal of Duhok University, 2019)
In all Kurdish research papers which were the analyzing of phrases and sentences are carried out by diagrams, the concepts of  lines and symbols through which this research was implemented were not clarified.In diagram analysis, every line has its own concept and form. To have more information on such concepts and to analyze Behdini Kurdish phrases and sentences by tree diagram and to identify the linguistic rules of sentences and phrases in Kurdish, we have tried to conduct this research according to descriptive analytical approach depending on the principles of grammar of Constituents and Transformational Generative Grammar.This research falls into four sections. In the first section, some samples of analysis by diagrams were shown and in the second section the concepts of lines used in this study were explicated. In the third section the linguistic rules of  Behdini Kurdish phrases were shown by tree diagram, whereas in the fourth section the linguistic rules of  Behdini Kurdish sentences were shown by tree diagram.The study has come up with some findings and conclusions, the most important of which is that there are eleven linguistic rules of analysis by tree diagrams in Behdini Kurdish distributed between sentences and nominal and verbal phrases.